Saddle Embolism in the Pulmonary Artery Bifurcation: Massive Pulmonary Embolism - Md Atiquzzaman, -; Faruq, Mohammad Omar; Ahmed, Kazi Nuruddin; Sohan, Md Ashikuzzaman; Zaman, Rifat; Akhtar, Farzana (Bangladesh Critical Care Journal, 2020)
Abstract Not Available Bangladesh Crit Care J March 2020; 8(1): 61-63